TEACHING VOCABULARY USING BANG-BANG GAME A PRE-EXPERIMENTAL STUDY ON THE SEVENTH GRADE OF SMPN 11 PONTIANAK - Handayani, Rifayetti; Susilawati, Endang; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to answer the research questionÂ  â€œhow effective is the use of bang-bang game to increase vocabulary achievement of the seventh grade students of SMPN 11 Pontianak?â€. The researchÂ  focused on the seventh grade students of SMPN 11 Pontianak in Academic Year 2017/2018 by administering a vocabulary test of common noun before and after the treatment given. In conducting this research, the researcher applied pre-experimental researchÂ  using one sample group with no control group. The data showed that the mean score of the studentsâ€™ post-test was (85.60) higher than studentsâ€™ pre-test (45.66).The research indicated that the effect size was categorized as moderate effect. The t-test (4.01) was bigger than the t-table (2.042). In conclusion, it is clear that the alternative hypothesis â€œThe use of bang-bang game as the teaching technique in teaching vocabulary is effective to increase studentsâ€™ vocabulary achievement was accepted, and the null hypothesis was rejectedâ€.Â Â Â Â Â Â Â Â Â Â Â Keywords: Bang-bang Game, Vocabulary,Â  Pre-Experimental StudyÂ